2013
DOI: 10.1007/s00114-013-1119-1
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in parasitism shapes larval immune function in a phytophagous insect

Abstract: Two of the central goals of immunoecology are to understand natural variation in the immune system among populations and to identify those selection pressures that shape immune traits. Maintenance of the immune system can be costly, and both food quality and parasitism selection pressure are factors potentially driving immunocompetence. In tritrophic interactions involving phytophagous insects, host plants, and natural enemies, the immunocompetence of phytophagous insects is constrained by selective forces fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…Similar to our work, some previous studies using a damselfly and a ground cricket have found higher PO activity in higher latitude populations (De Block et al, 2008;Fedorka et al, 2013). Conversely, increased PO activity in the south has been reported in the European grapevine moth (Vogelweith et al, 2013b).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our work, some previous studies using a damselfly and a ground cricket have found higher PO activity in higher latitude populations (De Block et al, 2008;Fedorka et al, 2013). Conversely, increased PO activity in the south has been reported in the European grapevine moth (Vogelweith et al, 2013b).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, lytic activity has previously been shown to vary less than PO activity, with the relative constancy having been primarily attributed to limited phenotypic plasticity in this trait (Triggs and Knell, 2012;McNamara et al, 2013a). Consistent with our observations on PP (but not the other two species), host plant has been shown to affect antimicrobial activity in a moth (Lobesia botrana; Vogelweith et al, 2013b) and lytic activity has been found to increase with temperature in Drosophila (Lazzaro et al, 2008;Fedorka et al, 2016). We are unaware of any studies showing among-population variation in lytic activity in insects, although a lack of variation has been reported for a crustacean (Daphnia magna; Mucklow et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, L. botrana population densities vary from year to year in various viticultural areas probably related to climatic conditions and might also change within relatively short distances (Roehrich & Boller, 1991). Recently, Vogelweith et al (2013) demonstrated a marked geographical variation in immune defences and extent of parasitism among different natural L. botrana populations, again indicating the high potential of this species to adapt locally to different biotic and abiotic selective forces. All these aspects make L. botrana a suitable model species for understanding genetic mechanisms of both range expansion and adaptation to host plants and local abiotic factors.…”
Section: Introductionmentioning
confidence: 98%